2021
DOI: 10.1371/journal.pone.0247166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new culture medium for isolation of nontuberculous mycobacteria from environmental water samples

Abstract: Nontuberculous mycobacteria (NTM) are waterborne pathogens commonly found in building water systems where they are a primary concern to vulnerable patient populations and can cause severe disease. The recovery of NTM from environmental samples can be a laborious undertaking and current pre-treatment methods and selective media lack sensitivity. We explored the use of the highly selective Rapidly Growing Mycobacteria (RGM) medium for culturing NTM from environmental water samples compared to existing methods. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…NTM Elite agar’s effectiveness in inhibiting non-AFB contamination is in keeping with a report by Alexander et al [ 19 ], showing that RGM medium generates much fewer samples with non-AFB growth (0.4%) than any other medium tested. In our study, however, we observed overgrowth in 9% of samples, which is somewhat higher than that reported by Alexander and co-workers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…NTM Elite agar’s effectiveness in inhibiting non-AFB contamination is in keeping with a report by Alexander et al [ 19 ], showing that RGM medium generates much fewer samples with non-AFB growth (0.4%) than any other medium tested. In our study, however, we observed overgrowth in 9% of samples, which is somewhat higher than that reported by Alexander and co-workers.…”
Section: Discussionsupporting
confidence: 88%
“…Recent evidence has shown that protocols based on rapidly growing mycobacterium (RGM) media can be highly effective in recovering NTM from potable and non-potable water samples [ 19 ]. More specifically, RGM medium alone, without pre-treatment, has been shown to afford higher sensitivity (~91%) and lower overgrowth of contaminating water-borne microorganisms compared to standard media.…”
Section: Introductionmentioning
confidence: 99%
“…Yield can be affected of course by the decontamination method due to sensitivity of some mycobacterial species to a decontamination agent [ 66 ]. Cultivation may be (and will be in further work) refined by using special cultivation media (e.g., RGM) [ 67 ]. For detection of mycobacteria by standard qPCR in these samples, the specificity was not high, perhaps unsurprisingly, as this method was primarily designed for less microbially loaded samples.…”
Section: Discussionmentioning
confidence: 99%
“…Purnanamasari et al [14] compared with the culture method, the Rema method had 80% sensitivity, 100% PPV (positive predictive value), and 97% NPV (negative predictive value). The feasibility study of the medium as a primary isolation media for mycobacteria, using MB BACT and Middlebrook 7h10 (MB7H10) and LJ medium, showed that the medium LJ was better and specific than the medium Middlebrook 7 H10 [15]. Antimicrobial susceptibility testing (AST) of Mtb has customarily been performed by the agar technique of proportion using the Lowenstein-Jensen (LJ) medium as bacterial culture medium by including the concentration the drug that has been suspended into the LJ medium.…”
Section: B Minimum Inhibitory Concentration (Mic) and Minimum Bacteri...mentioning
confidence: 99%